The Mindset of Intelligence Is Not a Contributor of Placebo Effects in Working Memory Training - Liu, Peibing; Zhang, Xin; Zhou, Renlai (Frontiers in Psychology, 2021)
Whether working memory training is effective in enhancing fluid intelligence remains in dispute. Several researchers, who doubt the training benefits, consider that placebo effects may be the reason for positive training gains. One of the vital variables that may induce the placebo effect is mindset of intelligence. Here we provide a test of whether mindset of intelligence leads to placebo effects in working memory training. Participants were overtly recruited and allocated to the growth mindset group or the fixed mindset group by Theories of Intelligence scale scores. A single, 1-h session working memory training is the cue to introduce the placebo effects. During pre/post testing, all participants completed tasks measuring working memory capacity (near transfer) and fluid intelligence (far transfer). Our findings show no significant difference between the two groups in both tasks. Therefore, these results suggest that placebo effect does not exist in the current study, which means individuals’ mindset of intelligence may not be a contributor to the placebo effect in 1-h working memory training. This research will help to further clarify the mechanism of placebo effect in working memory training.